Spatiotemporal evolution and driving force analysis of drought characteristics in the Yellow River Basin - Wang, Meiying; Chen, Yangbo; Li, Jingyu; Zhao, Yanjun (Ecological indicators, 2025)
•In 2000, YRB drought patterns shifted from intensification to easing.•From 1960 to 2022, the drought center remained in the midstreaml.•Cross-Wavelet and GeoDetector identified the spatiotemporal drivers of drought.•DEM and climate drive spatial drought; ENSO and AO affect temporal drought. Global warming intensifies extreme precipitation events, impacting society significantly, and drought is one of the most important stress factors for the ecological security of the Yellow River Basin (YRB). Understanding the time-domain abrupt changes and evolutionary mechanisms of drought events is crucial for comprehending the water resource dynamics in the basin. Taking the YRB as an example, we analyzed spatiotemporal variations in precipitation, identified abrupt changes, and calculated the 12-month standardized precipitation index (SPI12) to investigate drought evolution in the YRB. We identified four key drought attributes (number, duration, peak, and severity) utilizing the run theory. The spatial distribution of drought factors and typical drought events were identified, as well as the response of SPI12 to teleconnection and driving forces. The results indicate: Precipitation changed markedly around 2000, decreasing by 17.1 mm/10 yr before 2000, and increasing by 43.8 mm/10 yr thereafter. The maximum precipitation was also 1.95 times the minimum. Summer precipitation accounted for 53 % of the annual average. Downstream precipitation was 83.9 % and 25.3 % higher than that upstream and midstream, respectively. Spatial variation in precipitation was most notable upstream, with decreases concentrated in the north, impacting 24.9 %, and increases mainly in the south, covering 24.3 %. Short-term spatial changes were minimal, indicating gradual external influences. Abrupt changes in precipitation occurred in spring (1992), summer (1996), and winter (1970). Short-term cyclical fluctuations of 6–15 years were observed across distinct watersheds, with seasonal variations of 61 years for summer, 14 years for autumn, and 23 years for winter. The driest year was 2000, with an SPI12 of –1,35 in July. The center of drought activity is concentrated in the midstream, where it underwent two significant shifts: from the 1960 s to the 1980 s, the drought center moved northeastward, then shifted westward until the 2000 s, with longest displacement of 414.41 km to the east-northeast. This region had the highest drought frequency (15 events), total duration (225 months), and intensity (237) over the past 63 years. The SPI12 was influenced by the El Niño-Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and Arctic Oscillation (AO) before 2000, showing significant positive correlations with ENSO and AO, and a negative correlation with PDO. From 2000 to 2020, climate (q-value mean: 0.18) and DEM (q-value mean: 0.22) were the primary factors influencing drought variations, with climate interactions weakening and elevation interactions strengthening. This research provides crucial insights for effective water resource management and drought mitigation strategies in the Yellow River Basin.